Muscle power patterns in the mid-acceleration phase of sprinting - Johnson, M. D.; Buckley, J. G. (Journal of Sports Sciences, 2001)
To assess the role of the lower limb joints in generating velocity in the mid-acceleration phase of sprinting, muscle power patterns of the hip, knee and ankle were determined. Six male sprinters with a mean 100 m time of 10.75 s performed repeated maximal sprints along a 35 m indoor track. A complete stride across a force platform, positioned at approximately 14 m into the sprint, was video-recorded for analysis. Smoothed coordinate data were obtained from manual digitization of (50 Hz) video images and were then interpolated to match the sampling rate of the recorded ground reaction force (1000 Hz). The moment at each joint was then calculated using inverse dynamics and multiplied by the angular velocity to determine the muscle power. The results showed a proximal-to-distal timing in the generation of peak extensor power during stance at the hip, the knee and then the ankle, with the plantar flexors producing the greatest peak power. Apart from a moderate power generation peak towards toe-off, knee power was negligible despite a large extensor moment throughout stance. The role of the knee thus appears to be one of maintaining the centre of mass height and enabling the power generated at the hip to be transferred to the ankle.